Cranial Ultrasound Is an Important Tool in the Recognition of Life-Threatening Infratentorial Hemorrhage in Newborns - van Steenis, A.; Fumagalli, M.; Kruit, M. C.; Peeters-Scholte, C. M. P. C. D.; de Vries, L. S.; Steggerda, S. J. (Neuropediatrics, 2020)
Timely detection of severe infratentorial hemorrhage in neonates is crucial, especially in case of life-threatening brain stem compression and/or acute obstructive hydrocephalus, which need lifesaving neurosurgical intervention. Although the detection of infratentorial hemorrhage by ultrasound scanning is often considered as difficult, the use of additional acoustic windows and recognition of characteristic ultrasound features facilitate early diagnosis. In this case series, we report on newborns with severe, symptomatic infratentorial hemorrhage detected primarily by cranial ultrasound. We demonstrate the characteristic ultrasound features present in all cases and discuss how ultrasound diagnosis contributed to early diagnosis and treatment.
Keywords: ultrasound; infratentorial hemorrhage; term newborn